HBR's 10 must reads on strategic marketing - Larkin, Susan (Voice actor); Clark, Bernard Setaro, 1972- (HBR's 10 must reads (Series), 2022)
Stop pushing products-and start cultivating relationships with the right customers. If you read (or listen to) nothing else on marketing that delivers competitive advantage, listen to these ten articles. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you reinvent your marketing by putting it-and your customers-at the center of your business. Leading experts such as Ted Levitt and Clayton Christensen provide the insights and advice you need to: figure out what business you're really in; create products that perform the jobs people need to get done; get a bird's-eye view of your brand's strengths and weaknesses; tap a market that's larger than China and India combined; deliver superior value to your B2B customers; and end the war between sales and marketing.